Dinâmica espectral da soja por meio do NDVI utilizando sensores orbital e terrestre - Justina, Diego Domingos Della (2014)
Soybeans are an important agricultural crop, with expressive economical participation; thus, it is necessary the adoption of practices that enable crop forecasting, contributing for a better market position of this commodity. Remote sensing methodologies for monitoring production through are highly effective, due to their low cost, large-scale coverage and smaller time consumption. One of these techniques used is the NDVI Normalized Difference Vegetation Index, which has been employed on a large scale through use of the MODIS sensor. However, orbital sensors are subject to the influence of atmospheric factors and the culture dynamics, which may have different spectral behaviors among cultivars of the same species. In this context, non-orbital spectroscopy would be a viable solution for studying the existence of variations in the spectral behavior of any crop without further interference from exogenous factors. Thus, the aim of this work was to evaluate the temporal profiles of NDVI obtained with orbital MODIS sensor and non-orbital sensor GreenSeeker during the soybean development cycle. The study was conducted in two plots (T1 and T2) located on the Central Cooperative of Agricultural Research - COODETEC, in Cascavel State of Paraná. Samples of NDVI of thirteen pixels, three of them called pure pixels and ten non pure pixels, were taken at irregular intervals, but representing crop cycle. The data obtained by the non-orbital sensor were analyzed by exploratory analysis. Means of both orbital and non-orbital sensors were compared by test-t at 5% significance level. The means comparison test demonstrated the data obtained through the two sensors to be statistically different. However, both showed good dynamic range and sensibility to monitor and access spatial and temporal variations in the vegetation.